Biogeochemical Consequences of Nonvertical Methane Transport in Sediment Offshore Northwestern Svalbard. Issue 3 (21st March 2020) - Treude, T.; Krause, S.; Steinle, L.; Burwicz, E.; Hamdan, L. J.; Niemann, H.; Feseker, T.; Liebetrau, V.; Krastel, S.; Berndt, C.
Abstract: A site at the gas hydrate stability limit was investigated offshore northwestern Svalbard to study methane transport in sediment. The site was characterized by chemosynthetic communities (sulfur bacteria mats, tubeworms) and gas venting. Sediments were sampled with in situ porewater collectors and by gravity coring followed by analyses of porewater constituents, sediment and carbonate geochemistry, and microbial activity, taxonomy, and lipid biomarkers. Sulfide and alkalinity concentrations showed concentration maxima in near‐surface sediments at the bacterial mat and deeper maxima at the gas vent site. Sediments at the periphery of the chemosynthetic field were characterized by two sulfate‐methane transition zones (SMTZs) at 204 and 45 cm depth, where activity maxima of microbial anaerobic oxidation of methane (AOM) with sulfate were found. Amplicon sequencing and lipid biomarker indicate that AOM at the SMTZs was mediated by ANME‐1 archaea. A 1D numerical transport reaction model suggests that the deeper SMTZ‐1 formed on centennial scale by vertical advection of methane, while the shallower SMTZ‐2 could only be reproduced by nonvertical methane injections starting on decadal scale. Model results were supported by age distribution of authigenic carbonates, showing youngest carbonates within SMTZ‐2. We propose that nonvertical methane injection was induced by increasing blockage of vertical transport or formation of sediment fractures. Our study further suggests that the methanotrophic response to the nonvertical methane injection was commensurate with new methane supply. This finding provides new information about for the response time and efficiency of the benthic methane filter in environments with fluctuating methane transport. Key Points: Vertical methane gas transport in sediment was nonvertically detoured by impermeable blockages or through migration in sediment fractures Nonvertical injection of methane created two nonsteady state sulfate‐methane transition zones Anaerobic oxidation of methane responded commensurably to the additional methane supply